The traditional style of thirteenth-century Greek 'politikos stichos' poetry and the search for its origins. (4th April 2016) - Jeffreys, Elizabeth; Jeffreys, Michael
Abstract : It is with great pleasure that we join in saluting BMGS on the fortieth anniversary of its inception: it is a stalwart, valued presence in the international academic arena. Long may it continue!